Effect Of Foaming Agent Content And Fineness Modulus Of Sand On Mechanical And Physical Properties Of Foamed Concrete - جولاق نورا; علي ابراهيم خيربك (Latakia University Journal -Engineering Sciences Series, 2024)
Foamed concrete is categorized as a type of lightweight concrete, created by blending cement and sand with a foaming agent, that gives it the property of light weight compared to traditional concrete, it has various applications in construction field that differ from those of traditional concrete due to its varying densities. This research aims to investigate the influence of foaming agent content (foaming agent to cement ratio) and sand fineness factor on the physical and mechanical properties of foamed concrete, where the focus lies on studying dry density and compressive strength, and this will be accomplished by creating mathematical relationships between them. Eight mixtures were prepared with a cement content of 350 kg/m3, a water-to-cement ratio (W/C) of 0.56, and a sand-to-cement ratio (S/C) of 0.25. In the first four mixtures, the foaming agent to cement ratio was varied, using a single type of fine sand. In the next four mixtures, the foaming agent to cement ratio was fixed, while the type of sand varied based on the fineness modulus values, where Four sand types were used with different fineness modulus values. Various tests were conducted to determine certain physical and mechanical properties of foamed concrete, including wet density, dry density, and compressive strength. At the conclusion of this research, The findings highlighted the influence of foaming agent content and sand fineness modulus on the dry density and compressive strength values of foamed concrete. Additionally, Experimental mathematical relationships linking these parameters were also formulated.